Restorative Justice in Corporate Dispute Resolution as Business Actor in Indonesia - Abubakar, Lastuti; Afriana, Anita; Rajamanickam, Ramalinggam; Fakhirah, Efa Laela (Journal of Indonesian Legal Studies, 2024)
Indonesian limited liability company (Perseroan Terbatas or "PT") is a preferable entity selected by business actors in conducting activities. In this context, the characteristics of PT grant persona standi in judicio, as a legal subject capable of initiating and defending lawsuits in civil and criminal courts under Law No. 40 of 2007. Therefore, this article aimed to discuss the implementation of corporate accountability in the context of PT, and the potential for restorative justice in resolving disputes, relying on secondary sources such as theories, norms, and legal principles. The results show that 1) the application of restorative justice is consistent with the corporate entity's existence to maintain business continuity while upholding accountability as a legal subject, 2) Restorative Justice, centered on fundamental elements of encounter, repair, and transform, represents an effort towards the well-being and integrity of victims, perpetrators, and society. The method enhances legal certainty and protection for parties in PT-related business activities.